133k views
1 vote
Its a quadratic equation I Dont know exactly how to solve it help please

Its a quadratic equation I Dont know exactly how to solve it help please-example-1

2 Answers

5 votes
1. (X-2) (x+4)
= x (x+4) -2 (x+4)
= x2 +4x -2x -8
= x2 + 2x -8
2. (X+1) (x+6)
= x(x+6) +1 (x+6)
= x2 +6x +x + 6
= x2 +7x +6
3. (X-4)(x+2)
= x(x+2) -4 (x+2)
= x2 + 2x - 4x -8
= x2 -2x -8
4. (X+5)(x-3)
= x(x-3) +5 (x-3)
= x2 -3x +5x -15
= x2 +2x -15
5. (X-6)(x-2)
= x(x-2) -6(x-2)
= x2 -2x -6x +12
= x2 -8x +12

Regards,
ArmyCee:)
User Wolfgang Wu
by
4.3k points
3 votes

Answer:

Explanation:

(x - 2)(x + 4)

=x(x + 4) -2(x + 4)

=x^2 + 4x - 2x - 8

=x^2 + 2x - 8

(x + 1)(x + 6)

=x(x + 6) +1(x + 6)

=x^2 + 6x + x + 6

=x^2 + 7x + 6

(x - 4)(x + 2)

=x(x + 2) -4(x + 2)

=x^2 + 2x - 4x - 8

=x^2 - 2x - 8

(x + 5)(x - 3)

=x(x - 3) +5(x - 3)

=x^2 - 3x + 5x - 15

=x^2 + 2x - 15

(x - 6)(x - 2)

=x(x - 2) -6(x - 2)

=x^2 - 2x - 6x + 12

=x^2 - 8x + 12

User DeRagan
by
5.5k points